The 24-Hour Urinary 5-HIAA: A Simple Test With a Common Pitfall - Margaret L. Burks, MD; Shichun Bao, MD, PhD (AACE Clinical Case Reports, 2016)
ABSTRACT: Objective: 5-Hydroxyindoleacetic acid (5-HIAA) is the principal metabolite of serotonin, and the quantitative urinary excretion of 5-HIAA is the most useful way to diagnose serotonin overproduction by carcinoid tumors. The test carries a high specificity; however, many serotonin-rich foods, such as pineapple, banana, kiwi, and walnuts, will also increase urinary 5-HIAA excretion. We present a case which demonstrates that consumption of these foods prior to the 24-hour collection will falsely elevate the test results.Methods: Case report with literature review.Results: A 39-year-old female presented to endocrine clinic with episodes of hot “flushing.” She had no diarrhea, diaphoresis, skin rash, muscle weakness, or purple striae. Her primary doctor was concerned for carcinoid syndrome after a 24-hour urine 5-HIAA level was elevated to 22.7 mg/24 hours (normal, <6 mg/24 hours). After negative computed tomography and octreotide scans, it was felt that the patient's 24-hour urine 5-HIAA test was falsely elevated due to dietary intake. She was instructed to avoid serotonin-rich foods prior to her repeat urine collection. The subsequent 24-hour urine test returned within normal limits. She indeed did not have carcinoid syndrome. The patient continued to have “flushing” episodes of feeling short-winded and tremulous, which resolved with treatment for anxiety.Conclusion: To prevent false-positive results and avoid unnecessary testing and imaging, serotonin-rich foods should be avoided for at least 12 hours prior to urine collection. Biochemical tests for diagnosis of clinical syndromes should be interpreted with understanding of the potential for false-positive results.Abbreviations: 5-HIAA = 5-hydroxyindoleacetic acid CGA = chromogranin A CT = computed tomography